(untitled) (Innovation & Development in Engineering and Applied Science, 2024)
During the pandemic, universities had to change their teaching modality from face-to-face to virtual. This limited the opportunity to learn about digital manufacturing technologies in an experiential way. In response to this, the "Ruta Maker" program was adapted by incorporating ecosystems of learning resources for digital manufacturing. The objective was to know, in the students of the "Ruta Maker" program, the scope of a comprehensive ecosystem of virtual learning resources in strengthening technological skills, in adopting a maker in-house and DIY culture, and in the construction of open source digital manufacturing machines. It is a cross-sectional study, with intentional sampling, where four instruments were applied to 48 university students of the "Ruta Maker" program. Adequate level of learning was achieved in the program. On axis 1 "4.0 technological skills" the dimension "2D and 3D design" stood out (83%). On axis 2 "Experimentation spaces", the dimension "CNC MASLOW layout" had a better result than the other dimensions (83%). On axis 3 "DIY Culture Digital Manufacturing Machines", the two dimensions had similar achievements (73% and 71%). Student satisfaction values the Fabber Tech team and the accompaniment/prototyping more. In conclusion, digital manufacturing learning ecosystems in virtual modality, is a pedagogical option that allows digital design and manufacturing at home, promoting the Maker-DIY culture.